MANAJEMEN PENGELOLAAN SAMPAH (Studi Kasus pada Dinas Kebersihan, Pertamanan & Pemakaman Kota Jayapura - , Isak Wondiwoi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Waste management in regions is still ineffective yet there are no serious attentions from the city government in developing peopleâs awareness in reducing waste. Government support is highly required in order to give extra attention and assistance in socializing healthy waste management. Central and local governments are responsible in ensuring the waste management is done well, appropriate with the Law No. 18 Year 2008. Some problems related to waste management in Jayapura City is that there are still some who just throw their rubbish to the river, limited human resource and utilities, waste that brought to Nafri Dump are still less than the total waste production, the waste management service that still limited, workers payment that inappropriate with the job, and neither good planning, coordination, nor supervising are available. It can be concluded that waste management service in Jayapura City is not yet effective. Therefore, waste management service in Jayapura City needs to be assessed by doing case study to Jayapura City KPP Department This text is to assess and discover why waste management in Jayapura is not effective, with the target of the research is to assess the factors that affect the effectiveness, which caused the not effective waste management in Jayapura. From this conclusion result, researcher made assessment by using descriptive and qualitative research, because of that the case study should be characterized as explorative and descriptive research. In two months, researcher observe, interview, and study documents in KPP Department and another SKPD and Instances as well, including people of Jayapura The result shown that the factors that caused the ineffective waste management in Jayapura is that (1). Organization Management Factor, (2) Organization Environment Factor, either internal or external, (3) People Participation Factor, (4) Equipments and resources factor, and local law/regulations in waste management that is still not optimal From the conducted analysis, it can be concluded that the low application of management principles by DKPP, internal and external environment, low participation, inadequate tools and resources, low people participation and ineffective regulations implementation caused the ineffective Jayapura City waste management As the recommendation from this assessment, DKPP needs to socialize to the people, that the waste planning needs to paid attention and become an important part in building plan, and human resource development is also needed in DKPP, and junkyard and dump relocation, as well as the needed equipments that are currently inactive or less than required